Hericium ophelieae sp. nov., a novel species of Hericium (Basidiomycota: Russulales, Hericiaceae) from the Southern Afrotemperate forests of South Africa - B. Van der Merwe; P. Herrmann; Karin Jacobs (Mycology, 2023)
ABSTRACTA novel species of Hericium was recently collected in the Afrotemperate forests (Knysna – Amatole region) of Southern Africa. The novel species shares many similar, dentate features common to other species in Hericium, and its basidiome first appears stark white and yellows with age. However, the substrate choice and gloeocystidia and basidiospore sizes of the specimens collected were distinct from other Hericium species. This was confirmed by sequencing the ITS and 28S genetic markers, respectively. The novel species is described as Hericium ophelieae sp. nov. and appears unique as it grows on hardwoods indigenous to Southern Africa. The species has larger basidiospores and wider gloeocystidia compared to its closest relative. H. ophelieae sp. nov. is the first endemic species of the medicinal mushroom genus Hericium to be described from Southern Africa, and the second to be described from Africa, after its closest relative, H. bembedjaense, which was isolated in Cameroon. Although this is the first Hericium to be described from the Southern African region, there are likely others to be discovered, and this study highlights the need for further research into the fungal diversity of Afrotemperate environments.